Wednesday

July 23, 2014

July 23, 2014

Posted by **tabatha** on Sunday, October 27, 2013 at 7:00pm.

- math -
**Steve**, Monday, October 28, 2013 at 12:08am(h*g)(x) = h(x)*g(x)

So, just plug in x = -2:

((-2)^2+4)*(2(-2)) = (8)*(-4) = -32

or, more generally,

(h*g)(x) = (x^2+4)(2x) = 2x^3 + 8x

so (h*G)(-2) = 2(-8)+8(-2) = -32

**Related Questions**

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

math - Simplify sin^2x+cos^2x+sec^2x -tan^2x+csc^2x-cot^2x

math - if x is not equal to negative 3/2, (2x^3-x^2-6x)/(2x+3)equals? a. x-2 b. ...

math - translate and simplify"six less than twice the sum of a number and three...

math - Which equation demonstrates the commutative property of addition? a. 2x+y...

Math - Prove each identity: a) 1-cos^2x=tan^2xcos^2x b) cos^2x + 2sin^2x-1 = sin...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

math - how many times does the graph of y= 2x squared -2x+3 intersect the x-axis...

Math - Can someone please check this for mistakes please? y=4(x+3)-2x y=4x+3-2x ...